Kedudukan dan Kewenangan Badan Pembinaan Ideologi Pancasila sebagai State Auxiliary Organ (Lembaga Negara Penunjang) dalam Mengkaji Nilai-Nilai Pancasila - Muhammad Wahyu Hidayah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2025)
This study examines the position and authority of the Pancasila Ideology Development Agency (BPIP) as a state auxiliary organ within Indonesia’s constitutional system. The research focuses on the legal legitimacy and institutional position of BPIP in examining Pancasila values. This study employs a normative juridical method using statutory, conceptual and institutional approaches. The findings reveal that BPIP functions as an executive organ assisting the President and is established solely through a Presidential Regulation, resulting in weak institutional legitimacy. This condition creates potential overlapping authority and ambiguity regarding BPIP’s position within Indonesia’s constitutional structure.